Prevalência das Infecções Hospitalares no Centro de Terapia Intensiva do Hospital das Clínicas da Universidade Federal de Minas Gerais - Richardson Miranda Machado (2006)
This is a retrospective and descritive epidemiological study, which was carried on the Intensive Care Unity (ICU) for adult patients at Hospital das Clínicas from the Federal University of Minas Gerais State, its goals are to characterize the patients with hospital infections, determine the infections predominance and identify factors of risck related to the occurrence of the infections on the ICU. The study was carried on from the information gathering of the database (Epi-info, version 6.04), of the HospitalInfection Control Comission of HC/UFMG, where a new database was created from the gathered information, containing information about patients with hospital infection on the ICU, on the period between the years of 2000 and 2004. The sample was constitued of 282 patients corresponding to a predominance rate of 15%. Studies show that this population is even when related to sex and there was a predominanceof patients with ages between 41 and 65. Concerning the basis illness, heart diseases presented a higth percentage, followed by stomach and intestines ilnesses and neoplasias. Concerning the gravity of the clinical pathology classification, it was found that 98,2% of the evaluations corresponded to the higther gravity categories (D, C and E). The highter predominance of HI sires were pneumonias, followed byurinary system infections, arteriais infections and septicemias. On the cultivations Pseudomana aeruginosa, Staphylococcus epidermidis and Acinectobacter baumanii predominated. The risk factors strongly related to the hospital infections occurrence were the use of previous antimicrobial, the gravity of the basis illness, the invasive procedures and the time spend at the hospital before the moving to the ICU and thetime spend at the ICU.